RECONSTRUCTION OF DECISION BAPEPAM-LK NO. 412/BL/2010 CONCERNING ON THE TRUSTEE CONTRACT - Elvira Fitriyani Pakpahan; Bambang Tri Bawono; Azharuddin Azharuddin (Jurnal Pembaharuan Hukum, 2018)
The purpose of this study reconstructs Bapepam-LK's decision number 412 / BL / 2010concerning the trustee contract refers to specific provisions on guarantees stipulated byBapepam / FSA as in item 4 letter E which is still too common. Conditions of bail innumber 4 letter E Bapepam Decree 412 is only limited provision of information, not anecessity. Password Security (if any) does not provide legal certainty for investorsobligations in case of default. With juridical sociological research methods. The theoryused to analyze the theory of justice that is dignified, then research the reconstruction of the law done by changing the special provisions Bapepam's Decision No. 412 in number 4 letter E on collateral (if any) by removing / deleting the words in brackets (if any), caused not show the certainty justice and dignity justice.